Testing the Genomic Shock Hypothesis Using Transposable Element Expression in Yeast Hybrids - Drouin, Marika; Hénault, Mathieu; Hallin, Johan; Landry, Christian R. (Frontiers in Fungal Biology, 2021)
Transposable element (TE) insertions are a source of structural variation and can cause genetic instability and gene expression changes. A host can limit the spread of TEs with various repression mechanisms. Many examples of plant and animal interspecific hybrids show disrupted repression leading to TE propagation. Recent studies in yeast did not find any increase in transposition rate in hybrids. However, this does not rule out the possibility that the transcriptional or translational activity of TEs increases following hybridization because of a disruption of the host TE control mechanisms. Thus, whether total expression of a TE family is higher in hybrids than in their parental species remains to be examined. We leveraged publically available RNA-seq and ribosomal profiling data on yeast artificial hybrids of the Saccharomyces genus and performed differential expression analysis of their LTR retrotransposons (Ty elements). Our analyses of total mRNA levels show that Ty elements are generally not differentially expressed in hybrids, even when the hybrids are exposed to a low temperature stress condition. Overall, only 2/26 Ty families show significantly higher expression in the S. cerevisiae x S. uvarum hybrids while there are 3/26 showing significantly lower expression in the S. cerevisiae x S. paradoxus hybrids. Our analysis of ribosome profiling data of S. cerevisiae x S. paradoxus hybrids shows similar translation efficiency of Ty in both parental and hybrid genomes, except for Ty1_cer showing higher translation efficiency. Overall, our results do not support the hypothesis that hybridization could act as a systematic trigger of TE expression in yeast and suggest that the impact of hybridization on TE activity is strain and TE specific.